Transfer Pricing Tax Crime Risk in Mining Sector Companies : An Examination of Transfer Pricing Analysis and Capital Intensity - Ardi, Wijang; Maulida, Ulfa; Kusumaastuti, Maria Ulfah; Pahala, Indra; Wahono, Puji (Moneter: Jurnal Keuangan dan Perbankan, 2024)
This research investigates how capital intensity and transfer pricing may affect the likelihood of tax offenses in the mining industry. The report uses a sample of mining businesses listed from 2018 to 2022 on the Indonesian Stock Exchange (IDX) and using a quantitative research technique. The research examines the links between the dependent variable, which is represented by the cash effective tax rate (CETR), and the independent variables, transfer pricing (TP) and capital intensity (CAP), using multiple regression analysis and a legal approach. The corporations' transfer pricing methods and CETR vary significantly, according to descriptive data, indicating intricate dynamics in their tax management techniques. The results show a positive but statistically insignificant association between transfer price and CETR, which is consistent with contradictory findings from earlier research that supported and refuted the relevance of this relationship. The study's findings are important to policymakers because they imply that, despite transfer pricing's existence, its effect on tax evasion could not be as significant or clear-cut as previously thought. This realization necessitates a more sophisticated approach to mining industry compliance and regulatory frameworks, especially in environments like Indonesia. To get a deeper understanding of the changing dynamics of capital intensity and transfer pricing in influencing tax policies, future study should broaden its scope and include a wider range of factors over a longer time period.